Map Projections for Electronic Navigation and Other Marine GIS Applications - Pallikaris, Athanasios (The International Hydrographic Review, 2012)
The results of a research on the identification of suitable map projections for Electronic Chart Display and Information System (ECDIS) are presented. Eighteen map projections have been selected and evaluated according to criteria based on the calculation and analysis of distortion as well as on specific requirements for marine navigation. Six map projections are proposed for use in Electronic Navigation (e-Nav) systems together with specific selection rules based on the location and the extent of the area displayed on the screen. Additional map projections for potential use in other marine GIS applications are also identified and proposed.